Applications Of IMHOFLOT G-Cell Centrifugal Flotation Technology - Rainer Imhof; Michael Fletcher; Arun Vathavooran; Adrian Singh (The Southern African Institute of Mining and Metallurgy, 2007)
The Imhoflot G-Cell, a new development in the pneumatic flotation technology (which incorporates centrifugal forces in the separating vessel) is a recent innovation in the mineral processing world. The G-Cell was invented by Dr Rainer Imhof and commercialised by Maelgwyn Mineral Services Ltd. In a short time span a number of plants and units have been successfully commissioned in the mineral processing industry. In addition, a number of industrial G-Cell flotation plants are in the process of construction for the purpose of coal preparation and environmental remediation. In this paper two industrial installations have been highlighted together with a pilot plant test programme investigating ultra fine flotation recovery for a base metal operation.